Landiolol for managing atrial fibrillation in post-cardiac surgery - Fellahi, Jean-Luc (Eur Heart J Suppl, 2018)
Landiolol is an intravenous ultra-short acting beta-blocker which has been used in Japan for many years to prevent and/or to treat post-operative atrial fibrillation following cardiac surgery. The drug is now available in Europe. This article is a systematic review of literature regarding the use of landiolol in that specific surgical setting.